Growth factors as drugs for neurological and sensory disorders (John Wiley and Sons, 1996)
Degeneration of sensory receptors or of the nerves innervating them leads to a sensory deficit. Various strategies have been tried for promoting regrowth of sensory receptors, particularly in the eye and ear. The latest data from experimental studies in animals are presented in the book including applications of BDNF and CNTF in the eye and epidermal growth factor in the ear.
Ciba Foundation symposium ; 196
Keywords: Nervous System Diseases; nemoci nervového systému; Neuromuscular Diseases; růstové látky; neuromuskulární nemoci; Growth Substances; nemoci centrálního nervového systému; farmacie a farmakologie; Central Nervous System Diseases; neurologie